2016
DOI: 10.3844/ajbbsp.2016.196.205
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa-Butter-Equivalent Production from <i>Yarrowia lipolytica</i> by Optimization of Fermentation Technology

Abstract: In order to obtain the optimal control point for single-cell lipid production with fatty acid profile similar to cocoa butter, this study explored the effects of carbon source, nitrogen source, temperature, sterculic acid methyl ester, cobalt on cell growth and lipid accumulation of Yarrowia lipolytica. Glycerol and ammonium tartrate-yeast extract were chosen as carbon source and nitrogen source for production of cocoa butter equivalent. Gradual increase in temperature (20-35°C) resulted in growth reduction, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…As with Y. lipolytica LFMB 20, the bacterial consortium did not assimilate FA (C18:0) and similar findings have been reported for A. curvatum and Starmerella bombicola [47,53]. Williams et al [51] observed a transformation of FOG FAs from unsaturated to saturated forms perhaps due to microbial transformations by bacteria. Williams et al [51] observed a transformation of FOG FAs from unsaturated to saturated forms perhaps due to microbial transformations by bacteria.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…As with Y. lipolytica LFMB 20, the bacterial consortium did not assimilate FA (C18:0) and similar findings have been reported for A. curvatum and Starmerella bombicola [47,53]. Williams et al [51] observed a transformation of FOG FAs from unsaturated to saturated forms perhaps due to microbial transformations by bacteria. Williams et al [51] observed a transformation of FOG FAs from unsaturated to saturated forms perhaps due to microbial transformations by bacteria.…”
Section: Discussionsupporting
confidence: 71%
“…The main FAs were palmitic, palmitoleic, stearic, oleic and linoleic acids, which have also been shown as principal long chain fatty acids of FOGs or other fatty wastes [9,24,50,51]. The main FAs were palmitic, palmitoleic, stearic, oleic and linoleic acids, which have also been shown as principal long chain fatty acids of FOGs or other fatty wastes [9,24,50,51].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…; Aggelis 2010, 2011b;Wei et al 2017). Various strategies, including genetic engineering approaches, fermentations at low oxygenation level, employment of D9 desaturase inhibitors and cultivations on media rich in the FA C18:0 have been successfully performed in order to alleviate the above-mentioned disadvantage and create lipids with composition similarities with the cocoa butter (Moreton 1988;Davies et al 1990;Papanikolaou et al 2001;Papanikolaou et al 2003;Xiong et al 2015;Zhao et al 2016). Yeast lipid can also be employed for commodity uses such us biodiesel production.…”
Section: Oleaginous Micro-organismsmentioning
confidence: 99%